2020
DOI: 10.1111/1755-0998.13226
|View full text |Cite
|
Sign up to set email alerts
|

A GT‐seq panel for walleye (Sander vitreus) provides important insights for efficient development and implementation of amplicon panels in non‐model organisms

Abstract: Targeted amplicon sequencing methods, such as genotyping-in-thousands by sequencing (GT-seq), facilitate rapid, accurate, and cost-effective analysis of hundreds of genetic loci in thousands of individuals. Development of GT-seq panels is nontrivial, but studies describing trade-offs associated with different steps of GT-seq panel development are rare. Here, we construct a dual-purpose GT-seq panel for walleye (Sander vitreus), discuss trade-offs associated with different development and genotyping approaches,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 53 publications
(104 reference statements)
0
41
0
1
Order By: Relevance
“…Genotyping-by-sequencing methods, like Rapture, are a feasible way to obtain this level of diagnostic power in a non-model species and can provide reliable mixture estimates. Once stock differences are identified, markers from high-density marker panels can be filtered to identify smaller subsets of highly-informative markers that can be incorporated into even higher throughput genotyping-in-thousands (GT-seq) panels for long-term monitoring and annual mixed-stock assessments (Bootsma et al 2020). For this reason, we are optimistic that our approach will offer a new means for agencies managing fisheries with weak population structure to discern local spawning stocks such that their relative contributions can be quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping-by-sequencing methods, like Rapture, are a feasible way to obtain this level of diagnostic power in a non-model species and can provide reliable mixture estimates. Once stock differences are identified, markers from high-density marker panels can be filtered to identify smaller subsets of highly-informative markers that can be incorporated into even higher throughput genotyping-in-thousands (GT-seq) panels for long-term monitoring and annual mixed-stock assessments (Bootsma et al 2020). For this reason, we are optimistic that our approach will offer a new means for agencies managing fisheries with weak population structure to discern local spawning stocks such that their relative contributions can be quantified.…”
Section: Discussionmentioning
confidence: 99%
“…We then produced the final metabarcoding libraries using latter steps in the genotyping‐in‐thousands by sequencing (GT‐seq) protocol (Campbell et al, 2015) following Bootsma et al (2020). Briefly, each individual and plate was barcoded in a second indexing PCR, and barcoded products were normalized using SequalPrep DNA Normalization plates (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…We then produced the final metabarcoding libraries using latter steps in the genotyping-in-thousands by sequencing (GT-seq) protocol (Campbell et al, 2015) following Bootsma et al (2020). Briefly,…”
Section: Sequencing Library Preparationmentioning
confidence: 99%
“…STACKS parameters for all species were as follows: process_radtags (‐e SbfI, ‐c, ‐q, ‐filter_illumina, ‐r, ‐‐bestrad, ‐t 140), ustacks (‐‐disable‐gapped, ‐‐model_type bounded, ‐‐bound_high 0.05, ‐M 3, ‐max_locus_stacks 4, ‐m 3, ‐H, ‐p 32), cstacks (‐n 3, ‐p 6 ‐‐disable_gapped). These STACKs parameters were derived based on review papers by Mastretta‐Yanes et al ( 2015 ) and Paris et al ( 2017 ) and have been shown to work well for similar fish species with nonduplicated genomes (e.g., Bootsma et al, 2020 ). SNPs genotyped in >30% of individuals (parameter flag: ‐r 0.3) were exported with the subprogram populations in variant call format (vcf) files.…”
Section: Methodsmentioning
confidence: 99%